2020
DOI: 10.1002/adfm.202000933
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide‐Cyclic R10 Peptide Nuclear Translocation Nanoplatforms for the Surmounting of Multiple‐Drug Resistance

Abstract: Multidrug resistance resulting from a variety of defensive pathways in cancer has become a global concern with a considerable impact on the mortality associated with the failure of traditional chemotherapy. Therefore, further research and new therapies are required to overcome this challenge. In this work, a cyclic R10 peptide (cR10) is conjugated to polyglycerol‐covered nanographene oxide to engineer a nanoplatform for the surmounting of multidrug resistance. The nuclear translocation of the nanoplatform, fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“…The nuclear translocation of this nanomedicine was facilitated by the cR(10) peptide. Subsequently, a laser-triggered release of the loaded DOX results in efficient anticancer activity confirmed by both in vitro and in vivo experiments ( Tu et al, 2020 ). The biodistribution and photothermal effects of this nanomedicine were studied in HeLa-R tumor-bearing nude mice.…”
Section: Nddss Targeting Drug Efflux Pumps For Inhibiting Mdrmentioning
confidence: 91%
See 2 more Smart Citations
“…The nuclear translocation of this nanomedicine was facilitated by the cR(10) peptide. Subsequently, a laser-triggered release of the loaded DOX results in efficient anticancer activity confirmed by both in vitro and in vivo experiments ( Tu et al, 2020 ). The biodistribution and photothermal effects of this nanomedicine were studied in HeLa-R tumor-bearing nude mice.…”
Section: Nddss Targeting Drug Efflux Pumps For Inhibiting Mdrmentioning
confidence: 91%
“…The nucleus has been proved to be the main interaction site of most therapeutics. Therefore, it is highly expected that nuclear targeted NDDSs can provide a more effective strategy than ordinary cell membrane-targeted therapy (Wang et al, 2011;Ling et al, 2012;Li et al, 2018;Li H. et al, 2019;Tu et al, 2020). Tu,Z.…”
Section: Construction Of Nddss Targeting the Site Of Drug Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoplatform designed to overcome multidrug resistance consisting of R10 peptide conjugated to polyglycerol-covered nanoscale GO exhibited easier nuclear translocation due to R10 peptide; a laser-triggered release of the loaded DOX showed superb anticancer activity in vitro as well as in experiments performed in vivo. This nanoplatform was characterized with a high-loading capacity, controlled release of drugs, and photothermal properties [ 226 ]. NPs consisting of functional GO conjugated with PEG, FA and indocyanine green acting as photosensitizer fabricated for delivery of MutT homolog 1 (MTH1) inhibitor (6-(2,3-dichlorophenyl)- N 4 -methylpyrimidine- 2,4-diamine hydrochloride; TH287) and DOX applied in combined chemo-photodynamic therapy, inhibited the proliferation and migration of osteosarcoma cells, stimulated both apoptosis and autophagy by suppressing the MTH1 protein and enhanced ROS accumulation.…”
Section: Graphene Oxidementioning
confidence: 99%
“…Hyperbranched polyglycerol (hPG) as a highly functional and water‐soluble polymer has been used for the modification of 2D carbon nanomaterials. [ 26–32 ] Modifying MoS 2 with hPG can improve its functionality, biocompatibility and water dispersibility. Wang et al have shown that modification of MoS 2 via physical adsorption of hPG improves the physicochemical properties of this material.…”
Section: Introductionmentioning
confidence: 99%